Camping vs. Glamping Tourism: Providers’ Perspective in the United Kingdom - ADAMOVICH, Venera; NADDA, Vipin; KOT, Michal; HAQUE, Adnan ul (Journal of Environmental Management and Tourism, 2021)
Glamping is a relatively recent phenomenon in tourism and outdoor hospitality which has considerably developed in last ten years in the UK and is projected to continue growing in the future. This study intends to fulfil identified gaps in tourism research and offer contribution by exploring difference between camping and Glamping. The primary data is collected from the professionals operating in the tourism industry. The qualitative in-depth interviews were conducted using networking approach while adhering to the standards of ethical protocols. Respondents have expressed a shared understanding of the main difference:  camping involving a stage of bringing and setting up own accommodation, whereas Glamping suggests that the accommodation is pre-set to the guests’ arrival. Results also indicated a lack of agreement in defining Glamping accommodation types. Moreover, this research potentially may expand the literature by suggesting a refined definition of Glamping. The managerial implications are presented at the end.